Assessing the Socio-economic Effects of Reservoir Dam Construction, Case Study; Siahzakh in Divandareh, Iran - Peyman Akbarzadeh; Seyyed Hassan Kaboli (جغرافیا و پایداری محیط)
The socio-economic and environmental consequences of dam construction can be irreversible. The ecosystem of reservoir dams is only examined prior to the construction and the effects of post-construction are not investigated. The main purpose of this qualitative-quantitative research is to estimate the economical-social effects of siazakh dam on the people living in the surrounding area. The research’s statistical society in quantitative part includes the rural house supervisors (households). In this research, the whole population of 1659, including 350 family, was considered as the case study. By the Cochran formula, 183 of the households were determined, for including the error probability, 200 questionnaires were considered. Factor analysis and SPSS software packages were applied to analyze the data. The statistical society in qualitative part includes the councils (up and down streams), regional water office and village office (n=41). The mind map diagram technique, content analyzing and GIS software are used in order to analyze data. According to the results of a multi-criteria analysis, the most important positive effects of this project were improving the region's agriculture, providing drinking water, increasing the irrigated area, controlling the flood, increasing land value, improving tourism and the income level. The most significant negative impacts were forced displacement of upstream, the demolition of the main occupations of the upstream (livestock, agriculture), the creation of false occupations among residents, the destruction of mosques and schools, environmental damage and the cutting of trees and land ownership in upstream of the dam. The research shows the positive effects of the design on the bottom of the dam outweigh its negative effects, while the negative effects of the dam are more than its positive effects in the upstream of the dam. Irrigational cultivation in upstream of dam is decreased to half, while the area under cultivation got to 3.5 fold in downstream of dam. Extended Abstract 1-Introduction Water is a socio-economic commodity and essential in development; so, the optimum use of water resources is important. Construction of the dam with changes in the ecosystem has wide socio-economic and environmental consequences. It is essential to study and evaluate these effects, as the impacts might be irreversible. The main purpose of this research is to estimate the economical-social effects of Siazakh dam on people living in the surrounding area. 2-Materials and Methods The case study (Siazakh Dam) is located 7 km southwest of Diwandareh and 92 km from Sannandaj city in Kurdistan province in the west of Iran; the methodology of this research is descriptive-analytical with an overall qualitative-quantitative approach. The research’s statistical society in quantitative part includes the rural house supervisors (households) living upstream and downstream of the dam. In this research, the whole population of 1659, including 350 families, was considered as the case study. By the Cochran formula, 183 of the households were determined, for including the error probability, 200 questionnaires were considered. The statistical society in qualitative part includes the councils (up and down streams), regional water office and village office (n=41) which were chosen by Census. The mind map diagram technique, content analyzing and GIS software are used to analyze data in qualitative part; in quantitative part, to analyze the data we utilized factor analysis and SPSS software packages. 3-Results and Discussion According to the results of a multi-criteria analysis, the most important positive effects of this project were improving the region's agriculture, providing drinking water to the area, increasing the area under water, controlling the flood, increasing land value, improving tourism and improving the income level. The most significant negative impacts were forced displacement of upstream inhabitants of the dam, the demolition of the main occupations of the upstream inhabitants of the dam (livestock, agriculture), the creation of false occupations among residents, the destruction of mosques and schools, environmental damage and the cutting of trees and land ownership in upstream. The research shows the positive effects of the design on the bottom of the dam outweigh its negative effects, while the negative effects of the dam are more than its positive effects in the upstream. With the drainage of the Siazakh dam which led to the transformation of the dam to a recreational center and solved the problem of water deficit, recreational and industrial centers around the dam have grown; consequently, the profitable people have attempted to demolish the pastures to increase their land areas because of the increase in the price of the land around the dam. Saedi (2012) evaluates the economic consequences of the construction of the Taleghan Dam, and states the changes in the climate surrounding the dam and the positive influences of the dam on the ranges; however, the influx of large non-owners to the areas around the dam, excessive use of natural resources, waste going those resources, and competition for capturing the lands are the impacts of the dam construction. Accordingly, his study shows the same results in different regions. From the residents perspective and based on the results of the study, in order to reduce the effects of compulsory passage of residents of the upstream, it is necessary to take the following actions: resettlement of these residents near their original location, compensation to compensate the residents and providing new jobs among these residents to compensate for traditional occupations which has been lost due to the construction of the dam. Scudder (2012) reported that in fair accommodation, compensation should be paid and various development plans should be made to compensate the resettlement. 4-Conclusion The results of this study showed that the positive effects of the dam on the lower side are higher than the upstream and its negative effects on the upstream inhabitants are more than the downstream. Based on the view of the residents of the upper reaches of the dam, the loss of houses, farms, gardens, pastures and livestock due to the dam construction, is not compensated by existing arrangements. Buying the right of ownership and customary rights of upstream utilities cannot have a significant effect on the negative social and economic impacts of the project, so a comprehensive plan for post-construction management needs to be developed and implemented before the project is implemented.